Impact of mental health problems on covid 19 patients from an Islamic perspective - Zaki Hasan, Ahmad; Sauri Hussien, Sofian; Tajudin, Anas; Hilyati Alilah, Noor; Salleh, Kamarudin; Sunawari Long, Ahmad; Najib Abdul Kadir, Muhd; Noor, A.Y., Mohd; M.I.A.M., Kashim; Yusof, Muhammed; Rahim Ridzuan, Abdul; Rahman, Z., Ab (International Journal of Psychosocial Rehabilitation, 2020)
The COVID-19 pandemic is a major health crisis affecting several nations, with over 3,218,410 cases and 230,309 confirmed deaths reported to date. Such widespread outbreaks are associated with adverse mental health consequences. Keeping this in mind, existing literature on the COVID-19 outbreak pertinent to mental health was retrieved via a literature search of the PubMed database. Published articles were classified according to their overall themes and summarized. Doubt is a delicate whisper that persuades to do evil to God in time of COVID 19 disease. This subtle whisper can make an impact on one’s heart. The whisper is very dangerous if one is often missed remembrance of God and asks for help from Him. Once the devil had taken control of one’s heart and soul, a whisper would be difficult to handle and eventually lost to the whisper said. It is deviated from the teachings of Islam, whether through words, actions, and movements. At-tustari explains every past thought, whether good or bad without affecting a person is not a doubt. It is indeed everything that is done without God s.w.t; it is called the doubtful; and anyone who wants the world but does not succeed, it is also called a doubt. The cause of a doubt is triggered by angry feelings, which eventually become a disadvantage. Therefore, your heart should always be with God in all matters such as relating to food, drink, gifts, and other requests, which will give you a peace of mind to calm of stress in COVID 19 disease. According to Dr Kamal Gaffar, doubt doubts are divided into two forms; one of them is from the soul (can be removed from the heart) and one from the devil (can be eliminated through remembrance of Ar-Rahman).